¿Is it necessary to analyze the relationship between mathematics teacher and the shaping of attitudes and the beliefs toward this discipline? - Gamboa-Araya, Ronny (Uniciencia, 2016)
Problems associated with teaching and learning mathematics have been a recurrent concern in several countries. The affective domain of students, in this context, has emerged as a relevant element that allows explaining some aspects of those problems. The need to explore in more detail the influence of teachers in the affective domain of students arises from this perspective, since what he/she does in the classroom could help strengthen or modify the attitudes and beliefs of students. This article aims to point out issues related to the affective domain in mathematics that have influenced teaching and learning the discipline, as well as the need to address them from the teaching staff perception. The purpose is to modify their work and encourage an image change of the discipline through their daily work. For this matter, conclusions of different investigations are presented showing the role of the affective domain, the influence of teaching staff and the need to carry out further research on the role of teachers.